Analyzing the Effects of Binge-Watching on Spousal Relationships - Qayyoum, Dr. Hayam; Dr Muhammad Riaz Raza; Ms. Fatima Inam Khan (Journal of Peace, Development and Communication, 2024)
This study analyzed the effect of Binge watching of spousal relationships. For this purpose, young and elder couples were selected to find the time spending in binge watching and degree of satisfaction and bonding among spouses. The results showed that the more time spend on binging series, the more is the degree of satisfaction and bonding which is not supported. Questionnaire was furnished among 150 sample size but 128 responses were collected. Uses and gratification was applied that shows that the spouses gratifying their need from the series but not from the spouses as they spend more time on watching the series. Moreover, spouses fulfill their affective need by binging Netflix series rather than talking or spending time with spouses. It has revealed that spouses are less satisfied and have less bonding among them and cannot fulfill affective need from the spouses. That is why spouses spend more time watching Netflix series.